ChemInform Abstract: Challenges and Strategies to the Total Syntheses of Fawcettimine‐Type and Serratinine‐Type Lycopodium Alkaloids. Issue 32 (18th July 2013) - Wang, Xiaoming; Li, Houhua; Lei, Xiaoguang
Abstract Review: ca. 100 refs.